Implementasi Menejemen Perencanaan Bagian Kerjasama dalam Mengembangkan Kemitraan di Pemerintahan Daerah Kabupaten Subang - Sartika, Ika; Zulfatus Shopiah, Nawa; Zulfa, Fitria; Farihin, Ahmad (STIT Fatahillah, 2025)
The implementation of planning management in the public sector, especially in the management of cooperation and partnerships, is very important to support effective and sustainable regional development of Subang Regency. the implementation of planning management is an important component of cooperation and partnership management. Using a qualitative descriptive methodology, this study aims to evaluate the role of planning management in building strategic partnerships in the Subang Regency Local Government. Inter-agency coordination, effective communication, and shared commitment from all stakeholders are critical to the success of partnerships between the Subang District Government and various groups. Organized and systematic partnership management by the Subang District Government can improve the efficiency of public services, enhance collaboration with strategic partners, and make a real contribution to sustainable development in the region. Good planning and management can work well together to improve working relationships and ensure that development programs are executed according to the needs of the Community